Antibiotic prophylaxis of acute postoperative endophthalmitis - V.P. Nikolaenko; D.F. Belov (РМЖ "Клиническая офтальмология")
V.P. Nikolaenko1,2, D.F. Belov1 1City Multidisciplinary Hospital No. 2, St. Petersburg, Russian Federation 2St. Petersburg State University, St. Petersburg, Russian Federation This paper reviews current aspects of antibacterial prophylaxis of acute endophthalmitis, a dangerous complication of cataract surgery. The lack of a common standard for preventing phaco infectious complications, a growing number of resistant bacterial strains, and legal aspects of the lack of some antibiotic formulations and routes of their administration with established efficacy in Russia account for the importance of this issue. The authors provide a list of primary causative agents of endophthalmitis and specify their antimicrobial susceptibility, highlight the importance of using antiseptics to prevent endophthalmitis, and describe in detail routes of administration of antibiotics, including conventional ones (subconjunctival injections, topical use) and whose actively promoted (intracameral, transzonular). In conclusion, the authors suggested a rational antimicrobial preventive algorithm for endophthalmitis after phaco based on the analysis of recent Russian and foreign published data and adapted to the Russian health care system. Keywords: phacoemulsification, endophthalmitis, antiseptic, antibiotic, prophylaxis, antibacterial resistance, fluoroquinolones, aminoglycosides, povidone-iodine, intracameral administration. For citation: Nikolaenko V.P., Belov D.F. Antibiotic prophylaxis of acute postoperative endophthalmitis. Russian Journal of Clinical Ophthalmology. 2021;21(4):220–226 (in Russ.). DOI: 10.32364/2311-7729-2021-21-4-220-226.